2011
DOI: 10.1245/s10434-011-1744-x
|View full text |Cite
|
Sign up to set email alerts
|

Normal PTH Levels in Primary Hyperparathyroidism: Still the Same Disease?

Abstract: Patients with pHPT and either elevated or normal PTH levels present with similar symptoms and calcium levels. The majority of patients with normal PTH have SGD, although adenomas are smaller. This may explain why patients with normal PTH values have less sensitive imaging and more frequently require four-gland exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 14 publications
9
36
2
5
Order By: Relevance
“…On the other hand, decreased 1.25(OH) 2 D 3 despite normal 25(OH)D indicating non-enhanced 25-hydroxyvitamin D 3 1-alpha-hydroxylase, and normal bone alkaline phosphatase pointing to absence of increased bone turnover, were not indicative of PHPT. Moreover, the serum concentration of intact PTH fluctuated spontaneously above and below the upper limit of the reference range in this patient, which was also observed in 13% (108/861) of patients with sporadic PHPT [4] in a previous study. Although a rare adult case of mild hypercalcaemia with a mutation in CaSR has been reported [5] , there was no inactivating mutation of CaSR in this patient.…”
supporting
confidence: 81%
“…On the other hand, decreased 1.25(OH) 2 D 3 despite normal 25(OH)D indicating non-enhanced 25-hydroxyvitamin D 3 1-alpha-hydroxylase, and normal bone alkaline phosphatase pointing to absence of increased bone turnover, were not indicative of PHPT. Moreover, the serum concentration of intact PTH fluctuated spontaneously above and below the upper limit of the reference range in this patient, which was also observed in 13% (108/861) of patients with sporadic PHPT [4] in a previous study. Although a rare adult case of mild hypercalcaemia with a mutation in CaSR has been reported [5] , there was no inactivating mutation of CaSR in this patient.…”
supporting
confidence: 81%
“…The true incidence of normohormonal PHP is very difficult to ascertain [14]. The reported incidence in the literature is 3-10.5% [6,13,14,18,23,24]. To our knowledge, the cohort of Amin [18] of 58 sporadic PHP patients with normal PTH levels is the largest reported in the literature to date.…”
Section: Discussionmentioning
confidence: 95%
“…In 1987, parathyroid-hormone-related peptide (PTHrp) has been isolated as a causative factor of malignant hypercalcemia [10]. Previous studies have suggested that this condition is a less symptomatic, lighter and weaker form of PHP [18].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, PTH levels are frankly elevated in cases with PHP, but in our case it was mildly elevated despite marked calcium elevation. This was unexpected, but in a study that compared patients with PHP having normal PTH levels with those having elevated PTH levels, the mean serum calcium levels and subjective symptoms were similar (32). Although mild-moderate hypercalcemia is frequent in (PHP), it should be noted that it can be severe and refractory to maximum medical treatment requiring emergency surgical intervention.…”
Section: Discussionmentioning
confidence: 96%